Secondhand hookah smoke: an occupational hazard for hookah bar employees. Issue 1 (25th January 2016) - Zhou, Sherry; Behrooz, Leili; Weitzman, Michael; Pan, Grace; Vilcassim, Ruzmyn; Mirowsky, Jaime E; Breysee, Patrick; Rule, Ana; Gordon, Terry
Abstract : Background: Despite the increasing popularity of hookah bars, there is a lack of research assessing the health effects of hookah smoke among employees. This study investigated indoor air quality in hookah bars and the health effects of secondhand hookah smoke on hookah bar workers. Methods: Air samples were collected during the work shift of 10 workers in hookah bars in New York City (NYC). Air measurements of fine particulate matter (PM2.5 ), fine black carbon (BC2.5 ), carbon monoxide (CO), and nicotine were collected during each work shift. Blood pressure and heart rate, markers of active smoking and secondhand smoke exposure (exhaled CO and saliva cotinine levels), and selected inflammatory cytokines in blood (ineterleukin (IL)-1b, IL-6, IL-8, interferon γ (IFN-γ), tumour necrosis factor (TNF-α)) were assessed in workers immediately prior to and immediately after their work shift. Results: The PM2.5 (gravimetric) and BC2.5 concentrations in indoor air varied greatly among the work shifts with mean levels of 363.8 µg/m 3 and 2.2 µg/m 3, respectively. The mean CO level was 12.9 ppm with a peak value of 22.5 ppm CO observed in one hookah bar. While heart rate was elevated by 6 bpm after occupational exposure, this change was not statistically significant. Levels of inflammatory cytokines in blood were all increased at postshift compared to preshift testing with IFN-Υ increasing from 0.85 (0.13) to 1.6 (0.25) (mean (standard error of the mean; SEM)) pg/mL (p<0.01). Exhaled CO levels were significantly elevated after the work shift with 2 of 10 workers having values >90 ppm exhaled CO. Conclusions: These results demonstrate that hookah bars have elevated concentrations of indoor air pollutants that appear to cause adverse health effects in employees. These data indicate the need for further research and a marked need for better air quality monitoring and policies in such establishments to improve the indoor air quality for workers and patrons.